Effects of strategies for reading comprehension on pupil's attitude and academic performance in English - Yaba, Cheriemay E. (CMU Graduate Journal, 2017)
The study aimed to determine the effects of strategies on the performance and attitude of grade six pupils in English. There were fifty one (51) grade six pupils of Lumintao Elementary School for the School Year 2014- 2015 were considered the respondents of this study. Quasi- experimental design was used. It involves pretest and posttest of fifty items (50) to determine the effects of the strategies on the performance of grade six pupils using mean, percent score and paired t-test. A survey questionnaire was also employed to identify the significant difference on the attitude of the pupils when expose to the strategies of reading comprehension. A lesson plan also that utilized the strategies for reading comprehension was used. The findings revealed that the mean score of the pupils had increased after they were exposed to the strategies of reading comprehension. Among the strategies, there were only five that showed high significant difference. The strategies were monitoring comprehension, metacognition, graphic and semantic organizers, recognizing story structure, and summarizing. It implied that the strategies had an effect to the performance of the pupils. However, there were two strategies such as answering question and generating question showed no significant on pupil's performance. This means that these strategies had no effect on the performance of the pupils. During the pretest, the attitude of the pupils was moderately positive towards English. After they were exposed to the strategies for reading comprehension, the attitude of the pupils turned to positive. It revealed that after the pupils being exposed to the strategies, they had a positive attitude towards English. The study concluded that there was a significant difference on the attitude of the pupil before and after exposed to the strategies.